SHOOT REGENERATION FROM ROOT EXPLANTS OF Adenocalymma nodosum (SILVA MANSO) L.G.LOHMANN - DE OLIVEIRA, JANAÍNA FERNANDA; BORGES DE PAIVA NETO, VESPASIANO; REZENDE ZUFFO, MÔNICA CRISTINA; MARQUES, MARIA RITA; NOLASCO RONDON, JOSIMARA; FERREIRA LIMA, SEBASTIÃO (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
A reproductible in vitro shoot regeneration system in Adenocalymma nodosum (Silva Manso) L.G.Lohmann using root explants was obtained in this investigation. Shoots were induced in vitro directly from root explants of 50-d-old seedlings on Murashige and Skoog (MS) medium through adventitious shoot bud regeneration. The ability of root explants to produce shoot buds occur without plant growth regulators addition. Shoot buds elongated into healthy shoots in the same induction medium. Results reforce hyphotesis that this species probably have an increased endogenous cytokinins biosynthesis.